Osobennosti gemodinamiki i reologicheskikh svoistv krovi u sportsmenov - Melnikov, A. A.; Vikulov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of the research was to reveal features, and interrelations of hemodynamics parameters and rheological properties of blood in athletes with the different orientation of training process (group "endurance" n=20 and group "power" n=10). Results have shown, that in relation to the control the greatest changes were revealed in the group "endurance": the decrease of the minute volume of blood, arterial pressure and the viscosity of blood, the increase of the general peripheral resistance of vessels at dilatation of cavities of a heart. In the group "power" there were marked the increase of arterial pressure and hematocrit at the increase of thickness of the back wall of left ventricle. The significant factor of the revealed intergroup distinctions was the index of weight of the body. The revealed interrelations between the viscosity of blood and hemodynamics parameters: in minute volume, the general peripheral resistance and arterial pressure - specify a significant role of fluidity of blood.